Influence of flexural steel reinforcement ratio on RC beams strengthened with externally bonded FRP sheets - Siddiqui, Nadeem A. (Journal of Structural Engineering, 2025)
In the field, RC beams are rarely balanced; they are either over-reinforced or under-reinforced. Under-reinforced beams are preferred over over-reinforced as former gives warning of impending collapse in case of overloading.However, due to being substantially under-reinforced these beams have lower flexural strength than desired and may require flexural strengthening. Use of externally bonded Fiber Reinforced Polymer (FRP) sheets for flexural strengthening of RC beams is one of the modern methods of strengthening. An investigation is, therefore, required to know up to what extent an under-reinforced beam can effectively be strengthened using FRP sheets. In the present study, for this purpose, nine RC beams were constructed in three groups with three ratios of reinforcing steel bars. The ratios which were used in three groups were 0.3, 0.5 and 0.7 of balanced steel ratio respectively. Each group had three specimens and all the beam specimens were designed not to fail in shear. Two of the three beams in each group were strengthened by externally bonding single layer of Carbon FRP (CFRP) sheets at the tension side of the beams. Third beam of each group was tested without strengthening as control beam. The effect of steel bars ratio on the performance of FRP sheets in upgrading the flexural capacity was then studied. The test results clearly indicate that flexural strength can be substantially improved by externally bonding the CFRP sheets to the tension face of under-reinforced RC beams. However, the percentage increase is dependent on steelreinforcement ratio. The flexural capacity of control and strengthened beams were also predicted using ACI-440 formulation. It was observed that ACI-440 prediction is conservative in nature, and matches well with the present experimental values.